2020
DOI: 10.1371/journal.pone.0234138
|View full text |Cite
|
Sign up to set email alerts
|

Shock wave impact on the viability of MDA-MB-231 cells

Abstract: Shock waves are gaining interests in biological and medical applications. In this work, we investigated the mechanical characteristics of shock waves that affect cell viability. In vitro testing was conducted using the metastatic breast epithelial cell line MDA-MB-231. Shock waves were generated using a high-power pulse laser. Two different coating materials and different laser energy levels were used to vary the peak pressure, decay time, and the strength of subsequent peaks of the shock waves. Within the tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Cavitation bubbles generated by acoustic waves may rupture the surrounding cell and induce cell lysis or cell membrane permeabilization [33]. Laser‐induced shock waves as a source of cell injury have been demonstrated previously, which is related to the pressure and the number of pulses [34, 35]. Doukas et al observed reduced cell proliferation and gross structural alterations in human lymphocytes and red blood cells after exposure to shock waves [35].…”
Section: Discussionmentioning
confidence: 99%
“…Cavitation bubbles generated by acoustic waves may rupture the surrounding cell and induce cell lysis or cell membrane permeabilization [33]. Laser‐induced shock waves as a source of cell injury have been demonstrated previously, which is related to the pressure and the number of pulses [34, 35]. Doukas et al observed reduced cell proliferation and gross structural alterations in human lymphocytes and red blood cells after exposure to shock waves [35].…”
Section: Discussionmentioning
confidence: 99%
“…Previous works provide additional insight into the possible working mechanisms. Membranes are sensitive to mechanical forces and shockwaves have been shown to change membrane permeability through the forces induced, which result in relative motion [ 50 ]. An analysis of the changes in the cell membrane associated with shockwaves indicates a non-uniform pressure distribution that creates pores on the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have described the possible role of LESW in cancer treatment [ 28 , 29 , 30 ]. LESW induces gene transfection through secreted microparticles [ 31 ].…”
Section: Discussionmentioning
confidence: 99%